Irisin, Fibroplast Growth Factor-21, and Follistatin Responses to Endurance Rowing Training Session in Female Rowers - Jürimäe, Jaak; Vaiksaar, Sille; Purge, Priit; Tillmann, Vallo (Frontiers in Physiology, 2021)
Purpose: This study examined selected myokine responses to an endurance rowing training session, and whether metabolic demands of the acute aerobic rowing exercise together with training volume, aerobic capacity and body composition variables affect potential exercise-induced changes in the myokine levels in female rowers. Methods: Fifteen national level female rowers (18.3 ± 1.6 years; 172.0 ± 5.0 cm, 67.5 ± 8.8 kg; maximal oxygen consumption [VO2max]: 47.2 ± 7.9 ml.min.-1kg-1) performed a 1-h rowing ergometer exercise at the intensity of 70% of VO2max (distance: 12.1 ± 1.1 km; energy expenditure [EE]: 639 ± 69 kcal; heart rate: 151 ± 7 beats.min-1) followed by a 30-min recovery period. Venous blood samples were collected before and after exercise, and analyzed for irisin, fibroplast growth factor-21 (FGF-21) and follistatin conentrations. Results: Plasma irisin and FGF-21 concentrations were increased (by 8%; p = 0.013 and by 13%; p < 0.0001, respectively) immediately after the aerobic rowing exercise. Follistatin was significantly increased (by 11%; p = 0.001) only after the first 30 min of recovery. Exercise metabolic demand variables such as distance covered and total EE were correlated with the pre-to-post-exercise increases in FGF-21 concentrations (r = 0.52; p = 0.047 and r = 0.68; p = 0.005, respectively). Exercise-induced increases in irisin levels were related to aerobic capacity as measured by VO2max (r = 0.53; p = 0.041) and training stress as measured by weekly training volume (r = 0.54; p = 0.039) in female rowers. Conclusion: Acute negative energy balance induced by a single endurance rowing training session elicited significant increases in irisin, FGF-21 and follistatin levels in national level female rowers. While exercise-induced increases in FGF-21 levels were associated with exercise metabolic demand measures, exercise-induced increases in irisin concentrations were related to aerobic capacity and training stress measures in female rowers.